2017
DOI: 10.1177/1369148117701752
|View full text |Cite
|
Sign up to set email alerts
|

Simply a matter of context? Partisan contexts and party loyalties on free votes

Abstract: While recent studies suggest the party loyalties of Members of Parliament (MPs) influence voting behaviour on free votes independently of personal preferences, it remains to be seen to what extent party loyalties influence MPs' voting behaviour more generally. To this end, this paper examines the impact of the partisan context of the vote on the effects of party loyalties. Using data from 20 divisions decided largely as free votes and controlling for personal preferences using a survey measuring MPs' attitudes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…For unwhipped votes , existing studies mainly investigate the impact of personal and constituency preferences on the direction of MPs' voting decisions. Those preferences have either been measured directly using survey data (for personal preferences, see Raymond 2017a, 2017b; Raymond and Overby 2016; Raymond and Worth 2017; for constituency preferences, see Hanretty et al 2017) or approximated using sociodemographic characteristics of the MP (Arzheimer 2015; Baumann et al 2013, 2015; Bauer‐Blaschkowski and Mai 2019; Engler and Dümig 2017; Hibbing and Marsh 1987; Overby et al 1998; Plumb 2015; Preidel 2016; Wenzelburger and Fehrenz 2018) and/or the sociodemographic composition of an MP's constituency as proxies (Baumann et al 2013; Haider‐Markel 1999; Hibbing and Marsh 1987; Kauder and Potrafke 2019; Mai et al 2022; Overby et al 2011). In addition, the MPs' party affiliation has proved to be a significant predictor of voting in favor of permissive or restrictive morality policies, respectively (Engler and Dümig 2017; Cowley and Stuart 1997, 2010; Hibbing and Marsh 1987; Overby et al 1998; Plumb 2015; Raymond 2017a, 2017b; Raymond and Overby 2016; Raymond and Worth 2017).…”
Section: Party Loyalty and Legislative Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…For unwhipped votes , existing studies mainly investigate the impact of personal and constituency preferences on the direction of MPs' voting decisions. Those preferences have either been measured directly using survey data (for personal preferences, see Raymond 2017a, 2017b; Raymond and Overby 2016; Raymond and Worth 2017; for constituency preferences, see Hanretty et al 2017) or approximated using sociodemographic characteristics of the MP (Arzheimer 2015; Baumann et al 2013, 2015; Bauer‐Blaschkowski and Mai 2019; Engler and Dümig 2017; Hibbing and Marsh 1987; Overby et al 1998; Plumb 2015; Preidel 2016; Wenzelburger and Fehrenz 2018) and/or the sociodemographic composition of an MP's constituency as proxies (Baumann et al 2013; Haider‐Markel 1999; Hibbing and Marsh 1987; Kauder and Potrafke 2019; Mai et al 2022; Overby et al 2011). In addition, the MPs' party affiliation has proved to be a significant predictor of voting in favor of permissive or restrictive morality policies, respectively (Engler and Dümig 2017; Cowley and Stuart 1997, 2010; Hibbing and Marsh 1987; Overby et al 1998; Plumb 2015; Raymond 2017a, 2017b; Raymond and Overby 2016; Raymond and Worth 2017).…”
Section: Party Loyalty and Legislative Behaviormentioning
confidence: 99%
“…According to Dickinson, and based on Hirschman (1970), we define party loyalty as “a strong feeling of support and allegiance not directly related to agreement, or any immediate expected gain or loss, resulting from association with the object of loyalty” (Dickinson 2018, 344). Comparable to the party identification of voters (Raymond 2017a), it is a kind of moral commitment to one's own party, rooted in a self‐definition by a group in relation to another group (Crowe 1986). Some empirical studies have pointed to such effects as possible explanations for high unity scores in free votes on morality issues, arguing that party unity in free votes can only be rooted in a “social identity shared among co‐partisans” (Raymond and Overby 2016, 319).…”
Section: Party Loyalty and Legislative Behaviormentioning
confidence: 99%
“…It has long been observed that it is often, perhaps paradoxically, more difficult to govern with a particularly sizeable majority than with a tight majority that cannot afford any dissenters or dissent (see Helms, 2005: chs 6 and 7). Party loyalty on voting behaviour tends to be strongest when the outcome is anticipated to be close and consequential to the success or failure of a given bill (Raymond, 2017; see also Stecker, 2015). In parliamentary systems in which governmental ministers are to be drawn from the pool of parliamentarians, relatively small parliamentary majorities may also help to keep the number of members of parliament (MPs) who see their ambitions to be appointed to ministerial office disappointed relatively small.…”
Section: ‘Negative Resources’ and The Performance Of Political Chief mentioning
confidence: 99%